2013
DOI: 10.21608/jappmu.2013.70995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Bacteria on Aflatoxins in Broiler Chickens: Growth Performance, Serum Parameters and Histological Alterations

Abstract: The main objective of this study was to evaluate aflatoxin (AFs) removal ability of probiotic bacteria. Two hundred and seventy one-day-old (Ross 308) broiler chicks were randomly distributed among nine groups. The dietary treatments were: 1 control; 2&3 artificially contaminated diets with 0.5&1mg of AFs, respectively; 4&5 received oral gavages anaerobic caecal culture (probiotic). 6, 7, 8&9 AFscontaminated diets plus probiotic feed additive (AFS-PB). The criteria of evaluation included body weight gain (BWG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…El-Afifi et al [ 53 ] revealed that probiotics decreased the effect of AF on body weight gain and improved blood parameters, liver function, and renal function. Probiotic results support their findings.…”
Section: Resultsmentioning
confidence: 99%
“…El-Afifi et al [ 53 ] revealed that probiotics decreased the effect of AF on body weight gain and improved blood parameters, liver function, and renal function. Probiotic results support their findings.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Marai and Asker (2008) hypothesized that aflatoxin's negative effects on immunity could reduce globulin levels. As a result, probiotics enhanced blood parameters, renal performance, and liver functions while reducing the impact of AF on body weight increase, as demonstrated by El-Afifi et al (2013).…”
Section: Health Advantages Of Probiotic Usage In Aflatoxin Managementmentioning
confidence: 89%